The Impact of Consumer Confidence on Tourism: Evidence from Indonesia - Maulana, Ar Razy Ridha; Dharmawan, Hendra (Indatu Journal of Management and Accounting, 2025)
Understanding the drivers of tourism demand is crucial not only for economic policy but also for business strategy in tourism-related industries. This study investigates the impact of consumer confidence on tourism arrivals in Indonesia, with a specific focus on both short-term and long-term effects. Employing the Autoregressive Distributed Lag (ARDL) model, complemented by robustness checks using FMOLS, DOLS, and CCR methods over the period 2008–2023, the empirical findings reveal that the Consumer Confidence Index (CCI) has a strong, positive, and statistically significant effect on the number of tourist visits, particularly in the long term. The results remain consistent across multiple estimation techniques, confirming the robustness and reliability of the evidence. These findings highlight the strategic importance of consumer sentiment as a forward-looking behavioral indicator in tourism demand modeling. For policymakers and business leaders in the tourism sector, the study underscores the value of monitoring public economic sentiment to anticipate demand shifts and inform responsive strategies.